IMPROVING FITNEIMPROVING FITNESS AND CORPORAL AESTETHICS THROUGH THE HELP OF AEROBICAL EXTRACURRICULAR ACTIVITIESSS AND CORPORAL AESTETHICS THROUGH THE HELP OF AEROBICAL EXTRACURRICULAR ACTIVITIES - Ghervan Petru; Lazăr Andreea Gabriela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Abstract The purpose of this research paper is to improve the physical condition (fitness) and body aesthetics of a group of subjects - teenager girls - through the help of a series of aerobic exercises. Practiced repeatedly aerobics activities contribute to the development and maintaining of functional capacities, increased cardiovascular function and improves resistance to effort. Moreover, aerobics exercises help improving body aesthetics by achieving a successful developing index. The students that participated in this research have been submitted to a series of fitness exercises with the help of an aerobic programme. The aerobics sessions took place four times per week which each session lasting up to fifty minutes. The exercises took place in an aerobic fitness gym in Suceava - Energy Fitness Club. The program lasted for 6 months starting in November 2015 and ending in May 2016. In order to evaluate the recovery capacity after effort and cardiovascular resistance Dorgo index and Harvard Stept Test have been used. For the evaluation of the somatic side anthropometric measurements have been taken such as: waist perimeter, thigh perimeter, hip perimeter and IMC. And one more test was - Physical Activities Index who evaluates lifestyle regarding physical effort Furthermore calculations have been made of fat percentage, body muscular index and water percentage on the tested subjects. The outcomes of the final tests taken prove the efficiency of the applied aerobics programme.